2007
DOI: 10.1128/aem.01770-06
|View full text |Cite
|
Sign up to set email alerts
|

Global Effect of Indole-3-Acetic Acid Biosynthesis on Multiple Virulence Factors of Erwinia chrysanthemi 3937

Abstract: Production of the plant hormone indole-3-acetic acid (IAA) is widespread among plant-associated microorganisms. The non-gall-forming phytopathogen Erwinia chrysanthemi 3937 (strain Ech3937) possesses iaaM (ASAP16562) and iaaH (ASAP16563) gene homologues. In this work, the null knockout iaaM mutant strain Ech138 was constructed. The IAA production by Ech138 was reduced in M9 minimal medium supplemented with L-tryptophan. Compared with wild-type Ech3937, Ech138 exhibited reduced ability to produce local macerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 107 publications
0
71
0
Order By: Relevance
“…Indeed, several studies have demonstrated the importance of the different components of the auxin signaling pathway in resistance against biotrophs and necrotrophs (El Oirdi and Bouarab, 2007;Yang et al, 2007;Spoel and Dong, 2008;Cuzick et al, 2009;Truman et al, 2010;Kidd et al, 2011). Nevertheless, a direct, major role for IAA in plant susceptibility has not yet been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several studies have demonstrated the importance of the different components of the auxin signaling pathway in resistance against biotrophs and necrotrophs (El Oirdi and Bouarab, 2007;Yang et al, 2007;Spoel and Dong, 2008;Cuzick et al, 2009;Truman et al, 2010;Kidd et al, 2011). Nevertheless, a direct, major role for IAA in plant susceptibility has not yet been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…A role for auxin in plant disease has long been suspected since many pathogens produce auxin during interaction with their host and because auxin can modulate the plant defense response (Yamada, 1993;Yang et al, 2007;Kazan and Manners, 2009). Auxin signaling has also been shown to promote disease caused by a number of pathogens (Grant and Jones, 2009;Kazan and Manners, 2009), and several auxin signaling mutants are more resistant to necrotrophic and biotrophic pathogens than are wildtype plants (Navarro et al, 2006;Chen et al, 2007;El Oirdi and Bouarab, 2007;Wang et al, 2007;Cuzick et al, 2009;Kidd et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding plant-associated bacteria, IAA has been shown to determine changes in bacterial gene expression in the nongall-forming phytopathogen D. dadantii (formerly Erwinia herbicola) 3937 [57], in Agrobacterium tumefaciens [58,59] and in the plant growth-stimulating rhizobacterium A. brasilense [60], in which its ipdC gene has been the only bacterial gene reported to possess an AuxRE in its promoter, as observed in the auxin-responsive genes of plants [48]. Similarly, in the yeast Saccharomyces cerevisiae, several IAA-inducible genes are regulated at high IAA concentrations by the fungal transcriptional activator YAP-1, which is able to bind to their promoters to induce a switch towards invasive behavior, together with an arrest of cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms that produce IAA can influence the host plant and function as pathogens, symbionts, or growth regulators, depending on how their IAA production influences the concentration of the plant's endogenous IAA pool and on the sensitivity of the plant to auxin. Organisms such as Erwinia chrysanthemi, Pseudomonas savastanoi, and Agrobacterium tumefaciens are phytopathogens of many host plants (11,21,23,46). Other organisms, including Azospirillum brasilense and Pseudomonas putida GR12-2, have proven beneficial to plants, and many IAA producers have been shown to stimulate increases in root mass and/or length (20,37,44).…”
mentioning
confidence: 99%